Smartphone Addiction and Phubbing Behavior: Risks of Technology for Social Media Users - Putri Karisma, Sally; Susiati, Susiati; Tobing, Christine Masada Hirashita; Oktara, Tri Windi; Arifin, Deasy Dwi Cahyaningtyas; Melamita, Anisa; Nasri, Wa Ode Lili Andriani; Syahputra, Yuda (Kuras Institute, 2025)
The rapid development of technology, especially smartphones, has brought significant changes to the daily lives of students, both positively and negatively. One of the emerging negative impacts is the phenomenon of phubbing, which refers to the act of ignoring others in favor of engaging with a smartphone. The purpose of this study is to describe the contribution of smartphone addiction on phubbing behavior in students. The sample of this study was 225 grade VII students. Data on smartphone addiction and phubbing behavior were collected through two questionnaires, including the smartphone addiction instrument which amounted of 16 items and the phubbing behavior instrument which amounted of 15 items. Data were analyzed using SPSS software with linear regression techniques. The findings in this study are the significant contribution given by smartphone addiction to phubbing behavior, seen from the contribution given by smartphone addiction of 66% to phubbing behavior. In addition, the regression coefficient is positive, so it can be stated that an increase in smartphone addiction causes an increase in phubbing behavior.